2014
DOI: 10.7863/ultra.33.1.161
|View full text |Cite
|
Sign up to set email alerts
|

The Fetal Urinoma Revisited

Abstract: The Fetal Urinoma Revisited he fetal urinoma is quite rare and presents as an encapsulated fluid collection caused by the extravasation of urine into the perirenal spaces. Fetal urinomas are strongly associated with obstructive uropathy usually secondary to posterior urethral valves or ureteropelvic junction obstruction. 1,2 Urinomas have been associated with minimal or no function in the affected kidney. 3,4 A recent meta-analysis reported the probability of an ipsilateral nonfunctioning kidney to be as high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…The sonographic appearance of an urinoma is a featureless ellipsoid or crescent‐shaped cystic mass adjacent to the kidney and spine. Large urinomas can be difficult to image as they can distort and displace the kidney, with the direction of renal displacement indicating whether the urinoma is in the anterior or posterior paranephric space 4 . Furthermore, small urinomas can also be difficult to diagnose as they may mimic a dilated calyx in the setting of hydronephosis.…”
Section: Discussionmentioning
confidence: 99%
“…The sonographic appearance of an urinoma is a featureless ellipsoid or crescent‐shaped cystic mass adjacent to the kidney and spine. Large urinomas can be difficult to image as they can distort and displace the kidney, with the direction of renal displacement indicating whether the urinoma is in the anterior or posterior paranephric space 4 . Furthermore, small urinomas can also be difficult to diagnose as they may mimic a dilated calyx in the setting of hydronephosis.…”
Section: Discussionmentioning
confidence: 99%
“…The rupture of renal calyces can be due to microperforation of the renal pelvis with secondary extravasation of urine into the retroperitoneal spaces. The urinoma may act as a “pop‐off valve” and can be associated with preservation of some urinary function, if obstruction is located in lower urinary tract, but when obstruction is located in the ureteropelvic junction, the prognosis for renal function on the affected side is poor, as seen in this case …”
mentioning
confidence: 87%
“…The appearance of a urinoma on a US examination typically involves a cystic mass, which lies adjacent to the kidney and spine. In fact, Yitta et al stated that any fluid‐filled mass that touches the lumbar spine is presumed to be a urinoma. Magnetic resonance imaging is rarely used for diagnostic purposes and is reserved for cases in which US is unable to conclusively show the relationship of the kidney to the mass …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, it has recently been reported that the presence of a fetal urinoma suggests a poor prognosis for the ipsilateral kidney's functionality and that the probability of a nonfunctional, dysplastic ipsilateral kidney in these patients may be as high as 80%. 79,80 PUVs may be associated with renal dysplasia with or without cysts, which can be detected on US, preferably with the use of linear transducers. 75,76,81 VCUG remains the reference standard imaging for the diagnosis of PUV.…”
Section: Posterior Urethral Valvesmentioning
confidence: 99%